2020
DOI: 10.3390/ijerph17176266
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality among Fire Department of the City of New York Rescue and Recovery Workers Exposed to the World Trade Center Disaster, 2001–2017

Abstract: The World Trade Center (WTC) attacks on 9/11/2001 have consistently been associated with elevated rates of physical and mental health morbidities, while evidence about mortality has been limited. We examined mortality between 9/12/2001 and 12/31/2017 among 15,431 WTC-exposed Fire Department of the City of New York (FDNY) firefighters and emergency medical service providers (EMS), specifically assessing associations between intensity of WTC-exposure and mortality risk. Standardized mortality ratios (SMR) and 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In the 1980s, several studies on steel workers observed increased risks of laryngeal cancer in those who were exposed to acid mists, mainly sulfuric acid from pickling operations [ 5 , 10 , 11 , 12 ]. The result was later confirmed by studies on other steel workers [ 9 , 13 ], as well as other workers with exposure to acid mists from other manufacturing process [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1980s, several studies on steel workers observed increased risks of laryngeal cancer in those who were exposed to acid mists, mainly sulfuric acid from pickling operations [ 5 , 10 , 11 , 12 ]. The result was later confirmed by studies on other steel workers [ 9 , 13 ], as well as other workers with exposure to acid mists from other manufacturing process [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SMR for all causes combined of the study cohort was significantly smaller than 1 ( p = 0.01), which indicated a healthy worker effect, because the overall mortality of the cohort members was lower than the general population of the same sex and age group in Taiwan [ 10 ]. Such a health worker effect is common in studies on occupational cohorts and may be introduced by various causes.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of these and other chronic illnesses in WTC-exposed rescue/recovery workers has not resulted in elevated mortality rates, however, when compared with general populations. Studies conducted in three different WTC rescue/recovery worker cohorts and, most recently, in a large combined cohort of WTC rescue/recovery workers showed significantly lower than expected mortality among participants compared with USA, New York State and New York City populations 10–13. These findings may reflect healthy worker effects, a phenomenon in which workers experience better health outcomes than the general population because they were healthier at the time of their employment 14.…”
Section: Introductionmentioning
confidence: 94%
“…Colbeth et al [ 7 ] studied the mortality among Fire Department of New York City rescue and recovery workers. The researchers used NIOSH’s Life Table Analysis System to generate Standardized Mortality Ratios with the US general population as the comparison group.…”
Section: Mortality Among New York City Fire Department Workersmentioning
confidence: 99%